Immediate Versus Staged Complete Revascularisation during Index Admission in STEMI Patients with Multivessel Coronary Artery Disease: A Comparative Study - Hamid Ali Shah, Waqas Ahmed, Zohaib Ahmed, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Patients presenting with ST-elevation myocardial infarction (STEMI) and multivessel coronary artery disease pose a therapeutic dilemma regarding the timing of complete revascularisation. Immediate complete PCI may reduce recurrent ischemic events but is associated with longer procedure time and greater contrast exposure. Methodology: This prospective comparative observational study was conducted at the Department of Cardiology, Hayatabad Medical Complex, Peshawar from January 2023 to June 2023, on 82 patients with STEMI and multivessel disease. Participants were divided equally into two groups: Group A underwent immediate complete revascularisation during the index procedure, and Group B underwent staged revascularisation during the same admission or within three weeks. Demographic, clinical, angiographic, and procedural variables were recorded. Primary outcome was in-hospital major adverse cardiovascular events (MACE: all-cause mortality, reinfarction, stroke, urgent revascularisation). Statistical analysis was performed using SPSS version 26, with p < 0.05 considered significant. Results: The mean age was 58.3 ± 10.1 years in Group A and 59.8 ± 9.4 years in Group B (p = 0.46), with a male predominance in both groups. Clinical and angiographic characteristics, including Killip class, LVEF, and distribution of triple-vessel disease, were comparable (p > 0.05). Immediate PCI was associated with significantly higher contrast volume (190.6 ± 40.8 ml vs. 135.4 ± 32.7 ml, p < 0.001) and fluoroscopy time (24.5 ± 5.3 min vs. 18.1 ± 4.6 min, p < 0.001). In-hospital MACE occurred in 7.3% of immediate PCI group versus 12.2% of staged PCI group (p = 0.46), with no significant differences in mortality, reinfarction, or major bleeding. Conclusion: Immediate complete revascularisation during index admission produced similar in-hospital outcomes compared to staged PCI, with slightly lower numerical rates of MACE but greater procedural burden. These findings support the safety and feasibility of immediate PCI in appropriately selected STEMI patients, while underscoring the need for larger trials with longer follow-up to clarify long-term benefit. Keywords: STEMI, multivessel PCI, immediate revascularisation, staged PCI, MACE, coronary angiography.